Implementasi Metode Fun Learning Sebagai Upaya Meningkatkan Semangat Belajar Huruf Hijaiyah Di Madrasah Diniyah Tarbiyatul Athfal - Malikhatun Khasanah; Puji Ekawati; Wafiq Khofifah; Siti Fatimah; Faisal Faisal (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the increase in students' enthusiasm for learning hijaiyah letters using the fun learning method using letter cards for first grade students at Madrasah Diniyah Tarbiyatul Athfal. This research is a classroom action research carried out in four cycles. Each cycle consists of the stages of planning, implementing, observing, and reflecting. The subjects of this study were first grade students at Madrasah Diniyah Tarbiyatul Athfal. Data collection techniques with observation, interviews, and documentation. As for the evaluation, it was carried out at the end of the meeting with a letter guessing game on snacks containing questions. The validity of the data using the triangulation technique. In each cycle there is an increase from 41% to 86%. So it can be concluded that there is an increase in the spirit of learning of students in knowing hijaiyah letters with the fun learning method using letter cards.